Acesso motor ao recurso de comunicação alternativa: Opinião de profissionais em relação ao layout de figuras - Sankako, Andréia Naomi [UNESP]; Braccialli, Lígia Maria Presumido [UNESP] (FapUNIFESP (SciELO), 2017)
The use of adequate size and position of the alternative communication picture has been a frequent doubt among teachers and specialized professionals who work with children with cerebral palsy. This study therefore aimed to verify the opinion of professionals working with alternative communication regarding the adequacy of the size and layout of communication pictures for children with cerebral palsy. Six expert professionals in alternative communication participated in this study. A semi-structured interview was conducted. Data were analyzed using content analysis. Three categories and 11 subcategories were identified. The research identified that there is no standard size for pictures used in alternative communication; the selection of the ideal size of the pictures and the best layout are carried out by trial and error and there is no instrument or protocol for this purpose; to select the ideal size for the picture, three sizes are used: small, medium and large; the best position and the most commonly used is the center, in the same or above the eyes line; the worst position and the least used is below the eyes line; the horizontal arrangement of pictures is the most commonly used.
Motor access to alternative communication resource: Professional opinion on the layout of pictures
Keywords: Assistive technology; Cerebral palsy; Special education